Re-expression of CD14 in Response to a Combined IL-10/TLR Stimulus Defines Monocyte-Derived Cells With an Immunoregulatory Phenotype - Krakow, Sören; Crescimone, Marie L.; Bartels, Charlotte; Wiegering, Verena; Eyrich, Matthias; Schlegel, Paul G.; Wölfl, Matthias (Frontiers in Immunology, 2019)
Interleukin 10 is a central regulator of the antigen-presenting function of myeloid cells. It exerts immunomodulatory effects in vivo and induces a regulatory phenotype in monocyte-derived cells in vitro. We analyzed phenotype and function of monocytic cells in vitro in relation to the cytokine milieu and the timing of TLR-based activation. In GM-CSF/IL-4 cultured human monocytic cells, we identified two, mutually exclusive cell populations arising from undifferentiated cells: CD83+ fully activated dendritic cells and CD14+ macrophage like cells. Re-expression of CD14 occurs primarily after a sequential trigger with a TLR signal following IL-10 preincubation. This cell population with re-expressed CD14 greatly differs in phenotype and function from the CD83+ cells. Detailed analysis of individual subpopulations reveals that exogenous IL-10 is critical for inducing the shift towards the CD14+ population, but does not affect individual changes in marker expression or cell function in most cases. Thus, plasticity of CD14 expression, defining a subset of immunoregulatory cells, is highly relevant for the composition of cellular products (such as DC vaccines) as it affects the function of the total product.